South Korea pushes mobile broadband. - Cherry, S. (IEEE spectrum)
This paper describes a new wireless technology, called wireless broadband (WiBro), a mobile version of regular broadband. Developed in South Korea, WiBro is fundamentally similar to the standard known as WiMax, except that it allows the user to work a spreadsheet or watch a movie while trucking along at near-highway speeds. WiBro promises much higher data rates than a 3G cellular system, and a download rate that may eventually rise to about 18 Mb/s, fast enough for even high definition TV as well as voice, video, and email and Web traffic. Plans to establish WiBro service in South Korea's major cities are underway as many of the mobile data services customers begin to want more than mere 3G speeds.